One-Step Sputtering CuInGaSe 2 (CIGSe) Process for Thin Film Solar Cells: Progress and Challenges - Maliya Syabriyana; Zeni Ulma; Rosalia Dwi Werena (Proceeding of International Conference on Multidisciplinary Research, 2024)
The one-step sputtering for fabricating CuInGaSe2 (CIGSe) solar cells has been gaining attention due to its potential for simplifying the manufacturing process, large area uniformity, and environmentally friendly as less reliance on toxic Se precursors such as H 2 Se. Despite these advantages, several drawbacks remain. To date, devices fabricated by quaternary sputtering without additional selenization have been limited in efficiency to about 16%, and realizing bandgap grading in order to match the performance of the best evaporated devices presents a challenge. We discuss the prospects for quaternary sputtering as a fabrication technique for CIGSe and highlight areas of research that may result in improved performance. It also delves into the challenges faced in optimizing the material properties and device performance, and the ongoing research efforts to overcome these hurdles. The paper concludes with a perspective on the future directions for the field, emphasizing the importance of this research in the context of sustainable energy solutions.